System within systems: challenges and opportunities for the Expanded Programme on Immunisation in Pakistan - Zaeem Haq; Babar Tasneem Shaikh; Nhan Tran; Assad Hafeez; Abdul Ghaffar (BMC, 2019)
Abstract Background Pakistan has one of the highest infant and child mortality rates in the world, half of these occurring due to vaccine-preventable diseases. The country started its Expanded Programme on immunisation (EPI) in 1978. However, the programme's performance is often questioned, as the Immunisation rates have been chronically low and on-time vaccination unsatisfactory. We explored the programme's insights about its structural and implementation arrangements within the larger governance system, and the ensuing challenges as well as opportunities. Methods We carried out a qualitative case study comprised of semi-structured, in-depth interviews with 34 purposively selected key informants from various tiers of immunisation policy and programme implementation. The interviews revolved around WHO's six building blocks of a health system, their interactions with EPI counterparts, and with the outer ecological factors. Interviews were transcribed and content analysed for emergent themes. Results The EPI faces several challenges in delivering routine immunisation (RI) to children, including lack of clarity on whether to provide vaccination through fixed centres or mobile teams, scarcity of human resource at various levels, lack of accurate population data, on-ground logistic issues, lack of a separate budget line for EPI, global pressure for polio, less priority to prevention by the policy, security risks for community-based activities, and community misconceptions about vaccines. Conclusions The fulcrum for most of the challenges lies where EPI service delivery interacts with components of the broader health system. The activities for polio eradication have had implications for RI. Socio-political issues from the national and global environment also impact this system. The interplay of these factors, while posing challenges to effective implementation of RI, also brings opportunities for improvement. Collective effort from local, national and global stakeholders is required for improving the immunisation status of Pakistani children, global health security and the sustainable development goals.